The rational media selection as a new entrepreneurial opportunity: a theoretical foundation - Chaghouee, Yahya; Zarei, Behrouz (Nordic Journal of Media Management, 2022)
Purpose: The Goal of this paper is contributing the understanding of the concept of “Media Rational Value” in media selection process by customers. An extensive review of most of the relevant literature on media selection and their theories demonstrate a gap. It is that all of the media selection theories concentrate on the important factors from the business approach. There is a lack in explanation of key factors in media selection in business communications from customer perspective. Findings/Contribution: In this paper, by studying three constructs, i.e. information volume, information accuracy and information quality which all relating to “rational media value” the authors made an in-depth relationship between them and develop a model for media selection as costumers’ perspective. The relationships between the three constructs were developed and clarified how these factors shape rational media value. Additionally, an integrative model which is shaped by three constructs was developed.